Erythrocyte and Reticulocyte Indices on the LH 750 as Potential Markers of Functional Iron Deficiency - Eloísa Urrechaga; Luís Borque; Jesús F. Escanero (Anemia)
Reticulocyte hemoglobin content (CHr) and percentage of hypochromic cells (%Hypo) are restricted to the Siemens analysers. The aims of the study were to investigate the correlation of Red cells size factor (RSf) and low Hemoglobin density (LHD%), reported by Beckman-Coulter analysers, with CHr and %Hypo in the assessment of iron status in the presence of inflammation. 381 samples were run on both LH 750 (Beckman-Coulter) and Advia 2120 (Siemens) analysers. Correlation between parameters were calculated and the diagnostic performance of the new parameters was assessed. Results. Correlation between RSf and CHr, 𝑟=0.85. ROC curve analysis for RSf in the diagnosis of iron restricted erythropoiesis defined as CHr<28 pg: AUC 0.983; Cutoff 91.1%; Sensitivity 98.8%; Specificity 89.6% Correlation between LHD% and %Hypo, 𝑟=0.869. ROC curve analysis for LHD% in the diagnosis of iron deficiency defined by